2019
DOI: 10.3389/fpsyg.2019.01659
|View full text |Cite
|
Sign up to set email alerts
|

Performance Appraisal and Innovative Behavior in the Digital Era

Abstract: In digital competitive environments, organizations’ ability to innovate is more than ever the key to competitive advantage. One way to cope with this increased pressure for innovation is to capitalize on employees’ ability to generate new ideas and use these as building blocks for new and better products, services, and work processes. Individual innovation thus emerges as a key competence required from workers, in turn crucially affecting the way managers make employees contribute to organizational goals and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 48 publications
0
41
0
1
Order By: Relevance
“…A successful manager achieves important results for the organization by encouraging and leading the performance assessment. Therefore, regular monitoring and periodic assessment of the performance, creating a culture of the performance assessment, could help the managers understand if they were on the right way to improving their professionalism [38] and PHC outcomes [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful manager achieves important results for the organization by encouraging and leading the performance assessment. Therefore, regular monitoring and periodic assessment of the performance, creating a culture of the performance assessment, could help the managers understand if they were on the right way to improving their professionalism [38] and PHC outcomes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence from this study could be useful for policy makers for the formulation of adequate frameworks for managerial performance assessment and for the identification of the needs for continued managerial education in order to provide competent PHC managers. Human resources development leaders should advocate investments in managerial competencies and should give much higher priority to management development [3][4][5]38,40]. Investment in the development of professional staff of quality managers and managerial teams is a key point for goal realization in PHC in Serbia, as well as in many other countries that are to meet the majority of an individual's health needs over the course of their life and leave no one in their community behind [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the existent literature, latest focus is on electronic performance management systems, moreover of how automated and digitalized performance measurement may impact the efficiency of evaluation (Stone et al, 2015).Researchers considers that digitally transforming organizations need to adopt another strategy regarding their performance management systems, by changing their domain of interest on quantitatively results instead of traditional manner: never-ending working hours, overtime, pre-defined behavior. This way, the organization will show empathy on innovative work performance (Curzi, Fabbri, Scapolan, & Boscolo, 2019). In Table no.2 we can observe the advantages and the disadvantages of the evaluation based on objectives as a research based on the existing literature.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation based on objectives is considered more traditional than the 360-degree evaluation, because of the subjective opinion of the manager, who mostly establish the objectives of the employee. The biannual meeting is formal and lately, researchers observed that formality doesn't serve to a bigger understandability or transparency (Curzi et al, 2019). Moreover, formality fails to communicate what is decisive for the organization as they are too busy with the bureaucratic steps, tools and procedures of small meaning to employees and managers (Pulakos et al, 2015;Cappelli & Tavis, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…HR level) to ensure that the comments are not biased and to ensure that the sounds of appraises are taken into consideration. For instance, severely negative feedback is depleting the confidence of employees towards performance appraisal system and eventually reduces its effectiveness (Curzi et al, 2019;Deb, 2008). The final appraisal results are discussed with employees and are given chance to question any misinterpretation during the performance appraisal session.…”
Section: Figure 1: Performance Appraisal Processmentioning
confidence: 99%